LINGUISTIC TURN AND PHILOSOPHICAL INVESTIGATIONS - Nandhikkara, Jose (Journal of Dharma, 2009)
Language-use is such an impressive and fascinating human capacity that human beings are called homo loquens - speaking beings. Speaking is not only natural for human beings but also distinctive of human species, in fact, so distinctive that human being is defined in terms of the speaking: "man shows himself as the entity which talks. Language enables human beings, thus, to be precisely that living being which they are: as the speaking beings, human beings are human. Language provides a determinative characteristic to human nature: "the ability to speak is what marks man as man" and, according to Heidegger, language is the "foundation of human being